Exploring public health benefits of Dolichos lablab as a dietary supplement during the COVID-19 outbreak: A computational study - Elly Purwanti, Feri Eko Hermanto, Jantje Wiliem Souhaly, Wahyu Prihanta, Tutut Indria Permana (Journal of Applied Pharmaceutical Science, 2021)
The emerging case of coronavirus disease-19 (COVID-19) caused by the severe acute respiratory syndrome-coronavirus (SARS-CoV-2) virus has become a global health issue. Since there is no available developed vaccine, health-promoting foods play a vital role in maintaining the immune system against the disease. Dolichos lablab (DL), an unutilized highly nutritional legume, has an excellent potential to cope with this pandemic with various health benefit phytochemicals. This study appraised the possibility of phytochemical content from DL to prevent virus infection and hyperinflammation in COVID-19 in silico. DL’s phytochemicals from liquid chromatography–high-resolution mass spectrometry analysis were docked with several SARS-CoV-2 proteins, including main protease and HR. Also, NF-κB docking was executed to pursue anti-inflammatory properties. The drug-likeness properties of screened phytochemicals were then evaluated using SwissADME. According to the results, there were 16 phytochemicals with a high affinity to targeted proteins. Among those, five phytochemicals consistently gave a low binding affinity to all targeted proteins. Those five phytochemicals’ physicochemical properties, except for rutin and (9cis)-retinal, also coped with small-molecule bioavailability, permeability, and flexibility according to the SwissADME calculations. In conclusion, DL has a high probability of complementing the medical effort as dietary supplementation to modulate the immune system and prevent viral infection.
Keywords: COVID-19, Dolichos lablab, heptad repeat, main Protease,NF-B.